2017
DOI: 10.1139/apnm-2016-0445
|View full text |Cite
|
Sign up to set email alerts
|

Why do team-sport athletes drink fluid in excess when exercising in cool conditions?

Abstract: This study assessed the potential physiological and perceptual drivers of fluid intake (FI) and thirst sensation (TS) during intermittent exercise. 10 male rugby players (17 ± 1 years, stature:179.1 ± 4.2 cm, body mass (BM): 81.9 ± 8.1 kg) participated in 6x6 min small-sided games, ∆TS and FI was observed (r = 0.085, p = 0.841). These data observed in an ambient temperature of 13.6 ± 0.9C, suggest team sport athletes drink in excess of fluid homeostasis requirements and TS in cool conditions, however this was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…High inter-individual variability was observed for both fluid loss and intake during training sessions and it is worth mentioning that on some days, some athletes did succeed in compensating fluid loss by fluid intake during training, or even over-compensated on a rare occasion. A study by Bargh et al (2017) showed that rugby players tended to drink in excess of fluid loss when performing in a cold environment. However, these rugby players had demarcated drinking pauses, which was not the case in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…High inter-individual variability was observed for both fluid loss and intake during training sessions and it is worth mentioning that on some days, some athletes did succeed in compensating fluid loss by fluid intake during training, or even over-compensated on a rare occasion. A study by Bargh et al (2017) showed that rugby players tended to drink in excess of fluid loss when performing in a cold environment. However, these rugby players had demarcated drinking pauses, which was not the case in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the hydration requirements (in addition to fluid and electrolyte balance) of adult rugby players in both training and match-play scenarios are well documented (Cosgrove et al, 2014;Love et al, 2018;Meir & Halliday, 2005) there is limited research in youth rugby players. Bargh et al, (2017) investigated fluid losses and intake in ten academy male rugby league players (17 ± 1 years old) during rugby training, which consisted of 6 x 6-minute bouts of intermittent non-contact small-sided games (interspersed with 2 minutes passive rest; ~46 mins in total (Bargh et al, 2017). During training ad libitum drinking of fluids was permitted.…”
Section: Hydrationmentioning
confidence: 99%
“…Para finalizar, la hidratación es una actividad que los fisioterapeutas realizan en el equipo deportivo. Por ejemplo, se utilizan bebidas hidratantes para favorecer la homeostasis corporal y favorecer la ingesta de sodio y potasio las cuales están involucradas en la contracción muscular, al garantizar una adecuada ingesta de hidratantes se favorece la reducción de fatiga y contracturas musculares (14)(15)(16)(17)(18).…”
Section: Introductionunclassified